3-2(2x-3)+3(4x-1)=-20

Simple and best practice solution for 3-2(2x-3)+3(4x-1)=-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2(2x-3)+3(4x-1)=-20 equation:


Simplifying
3 + -2(2x + -3) + 3(4x + -1) = -20

Reorder the terms:
3 + -2(-3 + 2x) + 3(4x + -1) = -20
3 + (-3 * -2 + 2x * -2) + 3(4x + -1) = -20
3 + (6 + -4x) + 3(4x + -1) = -20

Reorder the terms:
3 + 6 + -4x + 3(-1 + 4x) = -20
3 + 6 + -4x + (-1 * 3 + 4x * 3) = -20
3 + 6 + -4x + (-3 + 12x) = -20

Reorder the terms:
3 + 6 + -3 + -4x + 12x = -20

Combine like terms: 3 + 6 = 9
9 + -3 + -4x + 12x = -20

Combine like terms: 9 + -3 = 6
6 + -4x + 12x = -20

Combine like terms: -4x + 12x = 8x
6 + 8x = -20

Solving
6 + 8x = -20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 8x = -20 + -6

Combine like terms: 6 + -6 = 0
0 + 8x = -20 + -6
8x = -20 + -6

Combine like terms: -20 + -6 = -26
8x = -26

Divide each side by '8'.
x = -3.25

Simplifying
x = -3.25

See similar equations:

| 6x+3=-5x+7 | | 7x-5=8x-14 | | (u+4)(u+4)=2u^2+17u+34 | | 6x+3=-5x+-7 | | 2x-3y-2z=4x+3y | | m/s | | -8x-x+5=14 | | 3x+50=2x+80 | | 8(4n+7)=27+3n | | X+y=27.5 | | 6[-3x+3+5(x+1)]=7x-5 | | 3x+50=2x*80 | | 5.7=3.2d-8 | | 13-7y=6 | | y=0.15x+10 | | 3(y-1)=2x+2 | | 39=-6(4n-3) | | w-5=5w-7 | | 24-3h=30 | | 3(y+1)=2x+3 | | (3a-7)-2(a+1)=5 | | 3(x+1)3=24 | | (x*40)+(x*15)=70000 | | 282/344 | | 2x(15)=30x | | 7(8-n)+8n=57 | | (1/7)^4x=343 | | -5x-13=-2+8(6x-8) | | x/64=15/100 | | =4a+16-(a-4) | | 3x+(25)+2x+(115)=180 | | -18+15= |

Equations solver categories